Unveiling the Significance of Gedung Sate Architecture within the Context of Sustainable Cultural Tourism - Ahmad Ghazy Dananjaya (Advances in Civil Engineering and Sustainable Architecture, 2026)
One of the iconic historical buildings in Bandung, Indonesia, known as Gedung Sate, represents a unique architectural fusion of European and local styles. As a significant cultural landmark and a major tourist destination, its preservation and management are paramount. This study aims to analyze the cultural significance of Gedung Sate's architecture and to evaluate its role within the framework of sustainable cultural tourism. This research employed a qualitative case study approach, utilizing architectural observation, semi-structured interviews, and documentary analysis. The analysis is guided by the cultural significance framework of the ICOMOS Burra Charter and supplemented by conceptual models of tourism impact. The findings reveal that Gedung Sate's significance is dualistic, derived from its value as both a colonial aesthetic masterpiece and a symbol of post-colonial national struggle. Furthermore, while tourism numbers appear sustainable, the analysis exposes significant vulnerabilities in the building's physical carrying capacity and socio-economic benefits. The novelty of this study lies in its application of the Burra Charter to a prominent Indonesian heritage site and its structured, critical evaluation of sustainable tourism that moves beyond simplistic metrics. This research contributes to the discourse on heritage management, offering insights for balancing preservation and tourism at similar sites.